Pengembangan produk UMKM risol Dangke untuk pemberdayaan ekonomi masyarakat Desa Lebang - Muh. Basyir Usman; Ahmad; Nurul Fatwa Jamaluddin; Mazlan Ahmad; Juliati; Mutmainna, Inah; Muh. Khaerul Fajran; Yanti; Mirjayadi I; Cahaya Amaliah Darwis (Jurnal Dedikasi Masyarakat, 2022)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in enhancing local economies, including in Lebang Village, Enrekang Regency. Fluctuating dangke sales lead to product spoilage and reduced community income. This service activity aims to develop an innovative "Dangke Spring Roll" product as a dangke-based diversification to stabilize the market and add value. Implementation methods include partner needs assessment, preparation of materials and equipment, recipe formulation, production training, and product trials. Results demonstrate successful Dangke Spring Roll production with crispy texture, savory flavor, and extended shelf life. Initial consumer evaluation shows an 85% satisfaction rate. In conclusion, Dangke Spring Roll is suitable for adoption as a village MSME product, with recommendations for ongoing assistance and digital marketing strategies.